2023
DOI: 10.1111/apa.16678
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐loop oxygen system in late preterm/term, ventilated infants with different severities of respiratory disease

Abstract: Compliance of achievement of SpO 2 targets in preterm infants is low, especially in maintaining the SpO 2 below the upper limits of the target range and avoidance of hyperoxemia. 1 Closed-loop automated oxygen control (CLAC) systems may provide a solution as their use in preterm infants has been associated with fewer desaturations, 2 increased percentage of the time spent within the target oxygen saturation range and fewer manual adjustments to the inspired oxygen concentration. 3,4 In the interim analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A randomised crossover study by Kaltsogianni et al, 4 evaluated closed‐loop automated oxygen control in 31 ventilated infants born late preterm and at term who had different severities of respiratory disease. They found that this method worked best when infants had more severe lung disease.…”
Section: Are We Ready To Use Routine Automated Oxygen Control In Neon...mentioning
confidence: 99%
“…A randomised crossover study by Kaltsogianni et al, 4 evaluated closed‐loop automated oxygen control in 31 ventilated infants born late preterm and at term who had different severities of respiratory disease. They found that this method worked best when infants had more severe lung disease.…”
Section: Are We Ready To Use Routine Automated Oxygen Control In Neon...mentioning
confidence: 99%
“…CLAC also increased the time spent in the target oxygen range by 34% in eight infants with a congenital diaphragmatic hernia and decreased the median duration of desaturations. The authors demonstrated that CLAC was more useful for near‐term infants with more severe respiratory distress, who required a FiO 2 of ≥0.30, than for those who had less need for oxygen 6 . The authors say the results are promising, but preliminary, due to the relatively small sample size.…”
mentioning
confidence: 98%
“…This issue of Acta Paedia trica contains a paper by Kaltsogianni et al 6 that provides the full findings from a closed loop automated oxygen control (CLAC) study of 31 mechanically ventilated near‐term infants born at 34 or more weeks of gestation. The interim data on the first 16 infants was published in the January 2023 issue of Acta Paediatrica 7 .…”
mentioning
confidence: 99%
“…Term and near-term infants with respiratory dysfunction represent a population with significant morbidity and mortality. 1 Whilst the efficacy of automated oxygen control in preterm infants is widely documented, 3 the significance of the present study is its application in term newborns, a population with only one published study, 4 and young infants with RTI, a previously unstudied but common inpatient population. The effects of exposure to excessive supplemental oxygen and resultant hyperoxaemia are often discussed in the context of pre-term infants, but the newborn lung and brain of term infants are also vulnerable to oxygen-induced injury, due to the production of reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…To our knowledge, only one study to date has examined whether term and near-term infants with respiratory insufficiency could gain benefit from automated oxygen control, finding a 19% increase in time in the SpO 2 TR. 4 We therefore aimed to compare the effectiveness of automated oxygen control with manual control in mature newborns with respiratory disease, as well as young infants with respiratory tract infection (RTI). We hypothesised that automated oxygen titration would result in a higher proportion of time in the SpO 2 TR than in manual control.…”
mentioning
confidence: 99%